PERAN KEUCHIK DALAM PENYELENGGARAAN PEMBANGUNAN DI GAMPONG LAWET KECAMATAN PANTE CEUREUMEN KABUPATEN ACEH BARAT - Aduwina Pakeh (Universitas Teuku Umar, 2015)
The role of keuchik gampong ( village head ) in the implementation of development in gampong lawet pante ceureumen sub-district district of aceh the west has been implemented well but need to be increased again. In this research, researchers found that keuchik gampong have undertaken the role well, where keuchik gampong actively down to pitch in communicating, coordinated , move , and provide the motivation to aparat-aparat gampong as well as to the community to participate in the implementation of development. Besides, gampong programs made by keuchik gampong can 's done well , directed , right on target and very help communities gampong lawet The results of the study others are identified of factors affect the role of keuchik gampong in the development that is by factors in support and inhibitors .By factors in support covering , location gampong lawet which is very strategic, potential the diverse and the volition the community to forward, the people of participation is a good enough .While inhibition factors, the low human resources whether it is the community and government officials gampong, and funds apbg to gampong lawet who do not in proportion to the extent needs.Keywords : Keuchik Gampong, development, Gampong Lawet, west Aceh